An environmental noise study in the industrial, commercial, residential areas and arterial roads in western Bogotá, Colombia - Guevara, Marco Andrés; Guevara, Fredy Alejandro (Revista de Investigación Agraria y Ambiental, 2018)
Noise pollution as byproduct of development and urban activity is related with a great amount ofeconomic, social and cultural variables, whose importance as stressing, and possible even dangerous,agent in human life has come to be recognized in the last decades. In this case the city of Bogotá is acapital city of Colombia, located in the center of the country. Is the largest city in Colombia and has asurface extension area of 1,580 km2. Bogotá is a very variable city in terms of economic and social levellocation, and use of soils in the city planning. The factors mentioned above makes Bogotá a very complexanalysis system for sound and noise pollution studies. Due the size of the city, in this study the westernarea of the capital district is analyzed through a sound measurements in 7 different selected types ofareas, involving commercial, transportation, industrial, residential and arterial roads. This study allowedto identify the arterial roads as one important source of noise in the city, possibly mainly due to the traffico heavy vehicles inside the city. The max harmful levels of sound reach values of about 85 dB in thementioned locations (Av. Ciudad de Cali, Av. Cll 13 arterial roads and Salitre – El Greco TransmilenioStation).